2015
DOI: 10.1128/jvi.00123-15
|View full text |Cite
|
Sign up to set email alerts
|

Detergent-Resistant Membrane Association of NS2 and E2 during Hepatitis C Virus Replication

Abstract: Previously, we demonstrated that the efficiency of hepatitis C virus (HCV) E2-p7 processing regulates p7-dependent NS2 localization to putative virus assembly sites near lipid droplets (LD). In this study, we have employed subcellular fractionations and membrane flotation assays to demonstrate that NS2 associates with detergent-resistant membranes (DRM) in a p7-dependent manner. However, p7 likely plays an indirect role in this process, since only the background level of p7 was detectable in the DRM fractions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 73 publications
(160 reference statements)
4
36
0
Order By: Relevance
“…Interestingly, in the present study, we showed that the GDP-but not GTP-bound form of Rab32 specifically interacted with HCV core protein and enriched core in Rab32-derived perinuclear aggregated structures and resulted in a high level of core protein expression. Our hypothesis also fits well with the study of Shanmugam et al showing that HCV core protein-associated detergent-resistant membranes may serve as platforms for virion assembly (24). Importantly, it has been previously reported that Rab32 localizes at the mitochondrion-associated membrane (MAM) and regulates MAM properties (14).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, in the present study, we showed that the GDP-but not GTP-bound form of Rab32 specifically interacted with HCV core protein and enriched core in Rab32-derived perinuclear aggregated structures and resulted in a high level of core protein expression. Our hypothesis also fits well with the study of Shanmugam et al showing that HCV core protein-associated detergent-resistant membranes may serve as platforms for virion assembly (24). Importantly, it has been previously reported that Rab32 localizes at the mitochondrion-associated membrane (MAM) and regulates MAM properties (14).…”
Section: Discussionsupporting
confidence: 76%
“…Rab32 is involved in the assembly step of the HCV life cycle. HCV core protein has been shown to be localized in the detergent-resistant membranes which are putative platforms for HCV particle assembly (23,24). In addition, HCV core protein is localized on the surface of lipid droplets (LDs) in virus-infected cells, and core proteincoated LDs aggregate in the perinuclear region which has been proven to be essential for virion assembly (30)(31)(32).…”
Section: Rab32 Level Is Increased In the Context Of Hcv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the delivery of TopFluor-cholesterol (TF-cholesterol), to ‘new’ versus ‘old’ NS5A foci as depicted in Figure 5A. TF-cholesterol is a fluorescent cholesterol analog that closely mimics membrane partitioning and trafficking of native cholesterol [31] and has been used to monitor cholesterol trafficking to HCV replication organelles [12, 32]. While TF-cholesterol trafficked to both ‘old’ and ‘new’ NS5A foci, TF-cholesterol colocalized preferentially with ‘old’ NS5A foci (Figures 5B and C), suggesting that replication organelles become progressively enriched in cholesterol over time.…”
Section: Resultsmentioning
confidence: 99%
“…They may also be involved in the attachment, entry, assembly, or egress of a variety of pathogens, including enveloped viruses (7)(8)(9)(10)(11). Lipid rafts have also been shown to be important for HCV RNA replication (12)(13)(14), and NA255, a lipophilic long-chain base compound that disrupts the de novo synthesis of sphingolipid, a major component of lipid rafts, prevents the association of HCV nonstructural proteins with lipid rafts and inhibits HCV RNA replication (15).…”
mentioning
confidence: 99%